2022
DOI: 10.2147/opth.s377541
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asthenopia and Its Relationship with Electronic Screen Usage During the COVID-19 Pandemic in Jazan, Saudi Arabia: A Cross-Sectional Study

Abstract: To assess the connection between the prevalence of asthenopia and the use of electronic devices in Jazan, Saudi Arabia, during the COVID-19 pandemic. Patients and Methods: Asthenopia prevalence and its connection to electronic screens during the COVID-19 pandemic were evaluated in an analytical, cross-sectional investigation among the Jazan population. The sample population included 784 participants. Due to the COVID-19 pandemic, a pre-tested, organized, and self-administered questionnaire was used as the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The current terminology for this syndrome is DES [ 7 ]. The emergence of the COVID-19 pandemic in late 2019 and early 2020 caused many changes in the lifestyles and academic strategies of teachers and students in universities and schools [ 19 - 21 ], including the more frequent and prolonged use of digital screens, with an expected increase in the prevalence of DES [ 6 , 22 , 23 ]. In the current study, 412 participants were analyzed (378 university students and 34 staff members), and 71.4% of them had symptoms of DES before the COVID-19 lockdown, which increased to 88.8% during the last month.…”
Section: Discussionmentioning
confidence: 99%
“…The current terminology for this syndrome is DES [ 7 ]. The emergence of the COVID-19 pandemic in late 2019 and early 2020 caused many changes in the lifestyles and academic strategies of teachers and students in universities and schools [ 19 - 21 ], including the more frequent and prolonged use of digital screens, with an expected increase in the prevalence of DES [ 6 , 22 , 23 ]. In the current study, 412 participants were analyzed (378 university students and 34 staff members), and 71.4% of them had symptoms of DES before the COVID-19 lockdown, which increased to 88.8% during the last month.…”
Section: Discussionmentioning
confidence: 99%
“…Eyestrain is one of the symptoms of computer vision syndrome, along with other symptoms such as irritation, burning sensation, dry eyes and blurred vision. 31 32 These symptoms occur more frequently with longer use of visual displays, viewing from a closer distance to the screen and glaring background luminance. 32 33 A previous study reported that the symptoms of eye discomfort following computer use were significantly worse than those after hard-copy viewing.…”
Section: Discussionmentioning
confidence: 99%
“…Asthenopia belongs to the category of "liver strain" and "eye fatigue" in Chinese medicine [10]. Therefore, ancient medical practitioners considered overuse of the eyes, dark depletion of the heart and blood and loss of moistening of the eyes as important etiological mechanisms of the disease [11].…”
Section: Discussionmentioning
confidence: 99%